Комплексна переробка яблучної сировини із застосуванням електротехнологій - Чук, Володимир Васильович (My University, 2004)
В дисертації представлені результати теоретичних та експериментальних досліджень підвищення ефективності комплексної переробки яблучної сировини шляхом застосування електротехнологічних процесів імпульсного електроплазмолізу яблучної тканини та електромембранної підготовки екстрагента для вилучення пектинових речовин із яблучних вичавок. In a thesis the results theoretical and experimental researches of pinch of efficiency of complex processing of malic raw material are submitted by application of master schedules of pulsing electroplasmolysis of a malic tissue and electromembranous opening-up of extragent for withdraw of pectic materials from malic vydavok. Is rotined, that at set effective parameters of pulsing electroprocessing of malic raw material the yield of malic juice after a molding plasmolysis mash increases on 10 %. Set, that usage of a modified bipolar membrane MMB-3 with the improved electrochemical performances, is penetrating softened waters and improved magnetohydrodynamic modes provides pinch of efficiency of process of electromembranous opening-up of extragent and economies of power consumptions.
Keywords: імпульсний електроплазмоліз; електромембранна обробка; яблучна сировина; яблучний сік; яблучний пектиновий екстракт; pulsing electroplasmolysis; malic raw material; malic juice; malic pectic extract